Enhanced Solar Energy Conversion Through Optimized Multijunction Photovoltaic Cells - Muhammad Aliff Hafeez Azman; Sim Sy Yi; Guo Xian Min; Lee Zhi Jie; Mohd Abdul Talib Mat Yusoh; Alvin John Lim Meng Siang; Alwin Soh Wei Yeow (International Journal of Integrated Engineering, 2025)
As technology advances, the demand for energy sources continues to grow. In response to this demand, renewable energy has emerged as a key solution, leveraging environmentally friendly methods such as photovoltaic technology. However, existing solar cells exhibit low efficiency and power conversion rates. This study aims to identify the optimal materials and number of junctions necessary to enhance solar cell efficiency through the multijunction concept, which has been modelled using Matlab Simulink. The research employed various equations to design solar cells, including calculations for energy bandgap, reverse leakage, short circuit current, open circuit voltage, and power output. The findings revealed that a quadruple junction utilizing specific semiconductor materials achieved an impressive efficiency of 58.84%, a notable improvement compared to the 11.03% efficiency of single-junction solar cells.